Durability and Sustainability of Cement-Stabilized Materials Based on Utilization of Waste Materials: A Literature Review - Penghui Wen (MDPI AG, 2021)
The utilization of waste materials in cement-stabilized materials (CSMs) is an important way to promote the sustainable development of road engineering construction and solve the environmental problems caused by the accumulation of waste materials. With the increasingly prominent global environmental problems, the exploitation of natural aggravate and the production of cement are subject to strict management and restrictions. Different waste materials, such as industrial and mining wastes, construction and demolition wastes, municipal wastes, waste rubber and waste fiber, are utilized in CSMs, and this is beneficial to promote the sustainable development of CSMs. In order to promote the rational application of waste materials in CSMs, this paper systematically reviews the research on the durability and sustainable development of CSMs. The types and mixing forms of waste materials reutilized in CSMs are discussed. The effect of different waste materials on the durability of CSMs is objectively evaluated. The potential challenges of sustainable development of CSMs are proposed. This review may help to alleviate the apprehension of road workers about the utilization of waste materials in CSMs and provide useful suggestions for the large-scale application of different waste materials.